Intracytoplasmic sperm injection in sturgeon species: A promising reproductive technology of selected genitors - Fatira, Effrosyni; Havelka, Miloš; Saito, Taiju; Landeira, José; Rodina, Marek; Gela, David; Pšenička, Martin (Frontiers in Veterinary Science, 2022)
Sturgeons are the most endangered group of animals and their wild populations continue to decrease. In this study we apply for the first time the intracytoplasmic sperm injection (ICSI), an assisted reproductive technology, in endangered and critically endangered sturgeons. Using various egg-sperm species combinations we performed different ICSI experiments with immobilized pre- or non-activated spermatozoa, single or many, fresh or cryopreserved. Then we evaluated the fertilization success as well as the paternity of the resulted embryos and larvae. Surprisingly, all experimental groups exhibited embryonic development. Normal shaped feeding larvae produced in all egg-sperm species-combination groups after ICSI using single fresh-stripped non-activated spermatozoa, in one group after ICSI using single fresh-stripped pre-activated spermatozoa, and in one group after ICSI using multiple fresh-stripped spermatozoa. ICSI with single cryopreserved non activated spermatozoa, produced neurula stage embryos. Molecular analysis showed genome integration of both egg- and sperm-donor species in most of the ICSI transplants. In all, ICSI technology could be used as an assisted reproduction for producing sturgeons to rescue valuable paternal genomes.